Implementation of Environmental Accountability in the Primary Consumer Goods Industry as a Foundation for Sustainable Development - Adelia Briliana Annisa Rachmawati; Shinta Permata Sari (Transpublika Publisher, 2026)
The attainment of the Sustainable Development Goals (SDGs) necessitates a harmonious balance between economic growth, ecological sustainability, and social welfare. This study examines the effects of Green Accounting, Environmental Performance, Environmental Cost, and Material Flow Cost Accounting on the achievement of the Sustainable Development Goals (SDGs) in non-cyclical consumer companies listed on the Indonesia Stock Exchange during the 2022-2024 period. A quantitative research approach with purposive sampling is employed, resulting in a sample of 138 companies. The findings illuminate the fact that Green Accounting significantly contributes to the achievement of SDGs through its effective integration into corporate practices. Moreover, Environmental Performance positively influences SDGs, indicating that improved environmental management reflects corporate responsibility toward environmental conservation and sustainable development. Environmental Cost does not influence Sustainable Development Goals given that the company has not spent environmental costs optimally in managing the environment. On the other hand, Material Flow Cost Accounting can impact the achievement of Sustainable Development Goals as a result of the company’s endeavors to minimize wastage. This study contributes to sustainable development in the non-cyclical consumer sector and creates a better environment. This study draws attention to the necessity of managing and implementing sustainable development to increase competitiveness and comply with regulations regarding environmentally friendly business practices in efforts to achieve the SDGs.